2000
DOI: 10.1159/000054081
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Systolic Hypertension from a Vascular Point of View

Abstract: Due to the results of antihypertensive intervention studies, isolated systolic hypertension (ISH) has gained new interest lately. Yet, apart from increased aortic stiffness, the specific pathophysiological features of ISH have remained largely undetermined. Therefore, we investigated the elastic properties of the vascular bed of an upper arm segment in uncomplicated ISH patients and matched normotensive controls using an electrical bioimpedance technique. Compared with the controls, the compliance of the arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Therefore, the decline in endothelial NO production with age may underlie some age-related arterial stiffening. Also, isolated systolic hypertension is a 'natural' consequence of aging, it is associated with increased aortic stiffness and is now recognised as a major risk factor for cardiovascular diseases [27]. In addition to age, all of these changes may play a complex role in the decrease of aortic elasticity especially for older patients, therefore the proportion of influence of age declined in the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the decline in endothelial NO production with age may underlie some age-related arterial stiffening. Also, isolated systolic hypertension is a 'natural' consequence of aging, it is associated with increased aortic stiffness and is now recognised as a major risk factor for cardiovascular diseases [27]. In addition to age, all of these changes may play a complex role in the decrease of aortic elasticity especially for older patients, therefore the proportion of influence of age declined in the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The situation becomes even more complex when one considers that high blood pressure frequently co-exists with other cardiovascular risk factors that may independently alter the structure and tone of arterial blood vessels [96,97]. A recent study [146] also indicates that the mechanical properties of arteries may differ in patients with isolated systolic hypertension in comparison with systo-diastolic hypertension.…”
Section: Hypertensionmentioning
confidence: 99%
“…Data from clinical studies indicate that ISH is a distinct syndrome with pathophysiological changes different from those in essential hypertension [23]. The main feature of ISH is a decreased distensibility of the aorta and large arteries with subsequent cardiovascular events [24,25].…”
Section: Isolated Systolic Hypertension As a Cardiovascular Risk Factormentioning
confidence: 99%
“…Framingham heart study has also demonstrated an increase in arterial stiffness due to aging or pathology and a decrease in arterial distensibility [27]. Though other studies have questioned the reduction in distensibility as a natural consequence of aging [23,28], the recent Framin-gham offspring study involved healthy individuals demonstrated age-related increase in aortic stiffness with little change in peripheral arteries [29]. It is not known whether the decreased distensibility or the elevation of systolic blood pressure occur first.…”
Section: Isolated Systolic Hypertension As a Cardiovascular Risk Factormentioning
confidence: 99%